METTL14-mediated N6-methyladenosine modification of SOX4 mRNA inhibits tumor metastasis in colorectal cancer - Chen, Xiaoxiang; Xu, Mu; Xu, Xueni; Zeng, Kaixuan; Liu, Xiangxiang; Pan, Bei; Li, Chenmeng; Sun, Li; Qin, Jian; Xu, Tao; He, Bangshun; Pan, Yuqin; et al. (Molecular cancer, 2020)
Colorectal cancer (CRC) is one of the leading causes of tumor-related death worldwide, and its main cause of death is distant metastasis. Methyltransferase-like 14(METTL14), a major RNA N6-adenosine methyltransferase, is involved in tumor progression via regulating RNA function. The goal of the study is to uncover the biological function and molecular mechanism of METTL14 in CRC. Quantitative real-time PCR (qRT-PCR), western blot and immunohistochemical (IHC) assays were employed to detect METTL14 and SOX4 in CRC cell lines and tissues. The biological functions of METTL14 were demonstrated using in vitro and in vivo experiments. Chromatin immunoprecipitation (ChIP), Transcrptomic RNA sequencing (RNA-Seq), m6A-RNA immunoprecipitation sequencing (MeRIP-Seq), RNA immunoprecipitation and luciferase reporter assays were used to explore the mechanism of METTL14 action. METTL14 expression was significantly downregulated in CRC and decreased METTL14 was associated with poor overall survival (OS). Both the univariate and multivariate Cox regression analysis indicated that METTL14 was an independent prognostic factor in CRC. Moreover, lysine-specific histone demethylase 5C(KDM5C)-mediated demethylation of histone H3 lysine 4 tri-methylation(H3K4me3) in the promoter of METTL14 inhibited METTL14 transcription. Functionally, we verified that METTL14 inhibited CRC cells migration, invasion and metastasis through in vitro and in vivo assays, respectively. Furthermore, we identified SRY-related high-mobility-group box 4(SOX4) as a target of METTL14-mediated m6A modification. Knockdown of METTL14 markedly abolished SOX4 mRNA m6A modification and elevated SOX4 mRNA expression. We also revealed that METTL14-mediated SOX4 mRNA degradation relied on the YTHDF2-dependent pathway. Lastly, we demonstrated that METTL14 might inhibit CRC malignant process partly through SOX4-mediated EMT process and PI3K/Akt signals. Decreased METTL14 facilitates tumor metastasis in CRC, suggesting that METTL14 might be a potential prognostic biomarker and effective therapeutic target for CRC.